Optimization of liquid fuel production from co-pyrolysis of oil palm fronds and expanded polystyrene using response surface methodology - Alisyah Putri Desvi Takahasi; Dieni Mansur; Wegik Dwi Prasetyo; Sabar Pangihutan Simanungkalit; Wido Lesar Ignasius Purba; Wahyu Anggo Rizal; Ariyanti Sarwono; Yelita Anggiane Iskandar (Case Studies in Chemical and Environmental Engineering)
The transformation of plastic and biomass waste into fuel promotes sustainable energy alternatives and efficient waste management. In this study, liquid fuel production from co-pyrolysis of oil palm fronds (PF) and expanded polystyrene (EPS) was experimentally investigated in a fixed-bed reactor. The effect of process temperature (T, 300–500 °C), and PF-to-EPS ratio (R, 0.1 to 9) on pyrolysis oil yield (YPO) and PAH's composition (PAHC) was studied using Response Surface Methodology (RSM) based on Central Composite Design (CCD). PF-to-EPS ratio (R) was found to be the most significant process parameter for determining the YPO, while T was the most influential process parameter affecting PAHC. The maximum pyrolysis oil yield of 80.11 wt% and minimum PAH composition of 20.63 % area was obtained at an optimum T of 395 °C and 0.1 R. The pyrolysis oil also contained benzene with a concentration below the established standards. The pyrolysis oil produced under optimum conditions had a calorific value of 41.56 MJ/kg, kinematic viscosity at 40 °C of 0.85 mm2/s, density at 15 °C of 0.93 g/cm3, water content of 0.24 wt%, acidity of 3.46 mg KOH/g, and a flash point of 26.05 °C. Pyrolysis oil can potentially improve gasoline's octane rating because of its high aromatic compound content.